2016
DOI: 10.1371/journal.pone.0149362
|View full text |Cite|
|
Sign up to set email alerts
|

Decreasing Hepatitis C Virus Infection in Thailand in the Past Decade: Evidence from the 2014 National Survey

Abstract: Hepatitis C virus (HCV) infection affects ≥ 180 million individuals worldwide especially those living in developing countries. Recent advances in direct-acting therapeutics promise effective treatments for chronic HCV carriers, but only if the affected individuals are identified. Good treatment coverage therefore requires accurate epidemiological data on HCV infection. In 2014, we determined the current prevalence of HCV in Thailand to assess whether over the past decade the significant number of chronic carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 39 publications
4
56
1
Order By: Relevance
“…Susceptible populations were persons with unsafe injection practices, inadequate sterilization of medical equipment in health care settings, and unscreened blood products. The risk of HCV transmission has decreased because of nationwide HCV screening of blood transfusions since 1992 and the discovery of interferon as a treatment for HCV [ 13 , 29 ]. A public health campaign and improvement in the public health care system has decreased the prevalence of HCV in intravenous drug users who shared needles [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Susceptible populations were persons with unsafe injection practices, inadequate sterilization of medical equipment in health care settings, and unscreened blood products. The risk of HCV transmission has decreased because of nationwide HCV screening of blood transfusions since 1992 and the discovery of interferon as a treatment for HCV [ 13 , 29 ]. A public health campaign and improvement in the public health care system has decreased the prevalence of HCV in intravenous drug users who shared needles [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, sample size of the studies is relatively small, in which additional epidemiology studies would have offered more accurate conclusions . Other endemic countries for GT6 are Vietnam, Thailand and Myanmar, although the most prevalent genotypes in Thailand, Myanmar and Vietnam are 3a, 3b and 1a, respectively . Interestingly, a recent study from Thailand reported the decline in prevalence of HCV by half in the past decades but opposed to other genotypes, GT6 turned out to have an increasing trend (9%‐34%) .…”
Section: Epidemiologymentioning
confidence: 97%
“…Other endemic countries for GT6 are Vietnam, Thailand and Myanmar, although the most prevalent genotypes in Thailand, Myanmar and Vietnam are 3a, 3b and 1a, respectively . Interestingly, a recent study from Thailand reported the decline in prevalence of HCV by half in the past decades but opposed to other genotypes, GT6 turned out to have an increasing trend (9%‐34%) . However, caution should be exercised regarding the increasing trend of HCV GT6 in Thailand since it earlier could have partly been due to selection bias and misclassification of GT6 as genotype 1b with as earlier genotypic assay .…”
Section: Epidemiologymentioning
confidence: 98%
See 1 more Smart Citation
“…The prevalence of HCV infection and its particular genotype varies between different countries and regions. In Thailand, recent surveys in 7 of Thailand's 76 provinces found approximately 759,000 anti-HCV + individuals and 357,000 who had viremic HCV infection (3,4), with genotype 3a predominant (36.4%). For genotypic distribution in Thailand, genotype 3 was predominant in southern Thailand, while, genotype 6 was more common in the North than the other regions (5).…”
Section: Introductionmentioning
confidence: 99%